Distal Femoral Replacement for Fractures Allows for Early Mobilization with Low Complication Rates: A Multicenter Review - Stancil, Ryan; Romm, Jacob; Lack, William; Bohnenkamp, Frank; Sems, Stephen; Cross, William; Cass, Joseph; Keeney, James; Nam, Denis; Nunley, Ryan; Fernando, Navin; Sassoon, Adam (The Journal of Knee Surgery, 2021)
Periprosthetic fractures around a total knee arthroplasty (TKA), comminuted and intra-articular femur fractures, or fracture nonunions in osteoporotic bone represent technically challenging problems. This is particularly true when the fracture involves a loose femoral component or the pattern results in suboptimal fixation potential. These clinical indications often arise in an older and comorbid patient population in whom a principal goal of treatment includes allowing for early mobilization. Limited data indicate that arthroplasty via distal femoral replacement (DFR) is a reasonable alternative to open reduction and internal fixation, allowing for early ambulation with low complication rates. We performed a retrospective review of trauma and arthroplasty surgeries at three tertiary referral institutions. Adult patients treated for the above with a DFR were included. Patients with active infection, open and/or high-energy injuries and revisions unrelated to fracture were excluded. Patient demographics, treatment details, and outcomes were assessed. Between 2002 and 2017, 90 DFR's were performed for the above indications with a mean follow-up of 24 months. Postoperatively, 80 patients (88%) were allowed to weight bear as tolerated, and at final follow-up, 9 patients (10%) remained dependent on a wheelchair. The average arc of motion at final follow-up was 95 degrees. There were seven (8%) implant-related complications requiring secondary surgeries: two infections, one with associated component loosening; one fracture of the hinge mechanism and one femoral component failure in conjunction with a patellofemoral dislocation (both requiring revision); one case of patellofemoral arthrosis in a patient with an unresurfaced patella; one periprosthetic fracture with associated wound dehiscence; and one case of arthrofibrosis. In each of these cases, only modular components of the DFR were exchanged. All nonmodular components cemented into the femur or tibia were retained. DFR provides a viable reconstruction option in the treatment of acute distal femur fractures, periprosthetic femur fractures, and fracture nonunions. We noted that in an elderly patient population with high comorbidities, the complication and secondary surgery rates remained relatively low, while allowing for immediate weight bearing.
Keywords: periprosthetic fracture; revision total knee arthroplasty; distal femoral replacement